Innovative Activity of Financial and Industrial Groups - Rudenko, Marina N.; Goloshchapova, Ludmila V.; Savvina, Oksana V.; Zamkovoy, Andrey A.; Chernikova, Natalia V.; Andryushchenko, Olga G. (International Journal of Economics and Financial Issues, 2016)
The creation of financial-industrial groups (FIG) is one of the most promising ways of overcoming the investment crisis in the country. FIG-like structure which can combine financial and industrial capital is established in order to ensure efficient (due to more efficient administration of financial resources) and accelerated development of science and industrial production. This is achieved by diversification into new industrial products and services to guarantee higher and sustainable profit. FIG acts as a tool for comprehensive and cost-effective capacity utilization of enterprises that have not received sufficient orders for the state needs, and targeted financial support. In modern Russia the urgency is the problem of creating in the economy competitive organizational structures. Financial-industrial groups are to become a key link in the institutional framework of the reformed economy, increase its competitiveness in both the global and domestic markets, to become promoters of the structural adjustment of the economy. The process of creation FIG requires significant assistance from the state. This poses the following challenges for public authorities: to remove all artificial obstacles to the unification of capital, to develop measures for the operational support of the process, to ensure its uniform distribution in various fields. Keywords: financial-industrial groups, innovation, enterprise economy, innovative activity JEL Classifications: G23, O14, O25